(x^2+5x-36)/(x^2-16)
=(x^2+9x-4x-36)/(x^2-4^2)
=x(x+9)-4(x+9)/(x+4)(x-4)
=(x-4)(x+9)/(x+4)(x-4)
=x+9/x+4
Hope this helps.
Answer:
1. y=3x-2 -> x= (y+2)/3
Step-by-step explanation:
You simply sub-in the m and b, then "reverse" the problem by doing the steps to get from the 2nd, to the first.
Answer:
0.7999989281
Step-by-step explanation:
x1 = cos^-1 (3/5)
x1= 53.13°
sin(53.13) = 0.7999989281
There is a 20 percent chance Angela will pull a red scarf, 60 percent chance she will pull a black scarf and 20 percent chance she will pull a white scarf. So if she pulls a red scarf then there will be a 18 percent chance she will pull a white scarf after.
I Hope this helps!